INTEGRATING SWOT AND AHP IN A PARTICIPATORY STRATEGY FOR DISSEMINATING FISHERIES PRODUCTIVITY INFORMATION IN SEGARA ANAKAN LAGOON, CILACAP REGENCY - Dewi, Rose; Hilmi, Endang; Putera, I Gede Suweda Anggana (Universitas Mataram, 2025)
The Segara Anakan Lagoon (LSA) is a coastal region characterized by unique ecological features and a high level of biodiversity in its fishery resources. Functioning as the estuarine outlet of the Citanduy River Basin, the lagoon receives substantial freshwater inflow laden with high sediment loads. This natural dynamic, compounded by anthropogenic activities from surrounding communities, has led to ecological degradation manifested in declining water quality, reduction of the lagoon’s water body, and increased nutrient accumulation, which in turn triggers eutrophication. Consequently, the fishery resource potential has diminished, adversely affecting the welfare of local fishing communities, as evidenced by a growing trend of occupational shifts from fishing to farming. This community engagement study, grounded in scientific research, aims to mitigate the rate of ecological degradation while promoting behavioral transformation toward a conservation-oriented mindset as a strategic measure to enhance the livelihoods of fishers. The methodology encompasses the development of thematic maps based on in situ ecological analyses, a SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis to identify the strategic conditions of the LSA area, and the application of the Analytical Hierarchy Process (AHP) to establish solution prioritization. All quantitative data obtained were disseminated to the local community through Focus Group Discussions (FGDs). Community perception and participation were evaluated using structured questionnaires, with subsequent statistical analysis performed to test the validity and reliability of the instruments. Through this participatory approach, it is anticipated that information on high-potential fishery zones and viable ecological management solutions can be effectively communicated, thereby enhancing the adaptive capacity of coastal communities for sustainable resource governance.